New insight for activity intensity relativity, metabolic expenditure during object projection skill performance. Issue 21 (2nd November 2018) - Sacko, Ryan S.; McIver, Kerry; Brian, Ali; Stodden, David F.
ABSTRACT: This study examined the metabolic cost (METs) of performing object projection skills at three practice trial intervals (6, 12, and 30 seconds). Forty adults (female n = 20) aged 18–30 ( M = 23.7 ± 2.9 years) completed three, nine-minute sessions of skill trials performed at 6, 12, and 30 second intervals. Participants performed kicking, throwing and striking trials in a blocked schedule with maximal effort. Average METs during each session were measured using a COSMED K4b2. A three (interval condition) X two (sex) ANOVA was conducted to examine differences in METs across interval conditions and by sex. Results indicated a main effect for interval condition ( F (5, 114) = 187.02, p < .001, η 2 = 0.76) with decreased interval times yielding significantly higher METs [30 sec = 3.45, 12 sec = 5.68, 6 sec = 8.21]. A main effect for sex ( F (5, 114) = 35.39, p < .001, η 2 = 0.24) also was found with men demonstrating higher METs across all intervals. At a rate of only two trials/min, participants elicited moderate physical activity, with 12 and 6-second intervals exhibiting vigorous PA. Demonstrating MVPA during the performance of object projection skill performance has potential implications for PA interventions.